Microwave absorbing behavior of glass fiber reinforced MWCNT-PANi/epoxy composite laminates. (2020) - Jelmy, E.J.; Lakshmanan, Mahadevan; Kothurkar, Nikhil K.
Abstract: MWCNT/PANI modified epoxy matrix was used to prepare glass fiber reinforced polymer laminates by wet-layup vacuum bagging method. The amount of the MWCNT/PANI in the epoxy matrix was varied from 0.5 to 3 wt% with respect to the epoxy-hardener system, where as the fiber amount kept constant. The electrical and mechanical properties of the laminates got enhanced after the addition of MWCNT/PANI in the epoxy matrix. The reflection loss has increased from −16 dB for the laminate with 0.5 wt% MWCNT/PANI to −30.1 dB for the one with 2 wt% MWCNT/PANI and thus the laminates can be used as radar absorbing material.